2010
DOI: 10.1007/s10654-010-9539-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the contribution of biomarkers of different metabolic pathways to risk of type 2 diabetes

Abstract: diabetes. Of these pathways the highest contribution was observed for adiponectin which contributed one third to the risk and that equal proportion was contributed by GGT and HDLcholesterol, although the contribution of inflammation was lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 49 publications
4
18
1
Order By: Relevance
“…Our data are in agreement with the previous observation that HDLC is associated with T2D [11,[13][14][15][16][17][18][19]. Recently, Hasse et al reported that genetically reduced HDLC was not associated with increased T2D incidence, suggesting that the corresponding observational association is due to confounding and/or reverse causation [12].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are in agreement with the previous observation that HDLC is associated with T2D [11,[13][14][15][16][17][18][19]. Recently, Hasse et al reported that genetically reduced HDLC was not associated with increased T2D incidence, suggesting that the corresponding observational association is due to confounding and/or reverse causation [12].…”
Section: Discussionsupporting
confidence: 93%
“…In two recent metaanalyses, the individuals in the highest HDLC quintile were no better protected from coronary heart disease than those in the 4 th quintile [9,10]. Epidemiological studies of the association between low HDLC level and risk of type 2 diabetes (T2D) have provided inconsistent results [11][12][13][14][15][16][17][18][19][20]; the reported associations have been positive [11][12][13][14][15][16][17][18][19], null [20], positive only in men [21,22], positive only in women [13,23], or even inverse [24]. Although increasing plasma HDLC levels have been suggested to reduce the risk of T2D [25], a recent trial showed that treatment with niacin, which raised HDLC, also raised blood glucose and T2D risk [26].…”
Section: Introductionmentioning
confidence: 99%
“…For the current analysis, we considered those biomarkers that have been shown to be mainly associated with T2D risk in the EPIC-Potsdam study (12,(14)(15)(16)(17)(18): liver markers [such as g-glutamyltransferase (GGT) and fetuin-A), biomarkers of dyslipidemia (such as HDL cholesterol and triglycerides), biomarkers of inflammation [such as C-reactive protein (CRP)], an adipokine (adiponectin), and several metabolites (amino acids; diacyl-, acyl-alkyl-, and lyso-phosphatidylcholines; and sphingomyelins). Furthermore, SHBG was investigated, given the strong evidence for an association with T2D risk in a Mendelian randomization analysis (19).…”
Section: Measurement Of Biomarkersmentioning
confidence: 99%
“…So far, in most studies, the strength of the association of single biomarkers has been evaluated while little is known regarding the contribution of biomarkers of different metabolic pathways relative to each other. Interestingly, among a given set of biomarkers of different metabolic pathways, a recent study estimated the relative contribution of each biomarker to risk of T2DM to be 32.1% for adiponectin, 23.5% for HDL-C, 21.5% for γ-glutamyltransferase and 15.5% for C-reactive protein [11]. Such information on the relative contribution of biomarkers is important when it comes to the decision about the development of measures to affect biomarkers of pathways that are meant to reduce diabetes risk.…”
Section: Editorialmentioning
confidence: 99%